Efficacy and Safety of 5% Minoxidil Alone, Minoxidil Plus Oral Spironolactone, and Minoxidil Plus Microneedling on Female Pattern Hair Loss: A Prospective, Single-Center, Parallel-Group, Evaluator Blinded, Randomized Trial - Liang, Xuelei; Chang, Yuan; Wu, Haixuan; Liu, Yi; Zhao, Jian; Wang, Leyi; Zhuo, Fenglin (Frontiers in Medicine, 2022)
Background: The efficacy of topical minoxidil (MX) on female pattern hair loss (FPHL) is limited. Combination therapy basing on topical MX is currently expected to provide better outcomes. Objectives: To assess whether the combined therapies including MX plus oral spironolactone (SPT) and MX plus microneedling (MN) have advantages in efficacy and safety over topical MX alone on mild-to-moderate FPHL with normal hormone level in blood and regular menstrual cycle. Methods: A prospective, single-center, parallel-group, evaluator blinded, randomized trial including 120 non-menopause women with proven FPHL (Sinclair class II-III) was performed in China. Patients were randomly assigned to three groups: MX group (5% topical MX alone, once daily), MX + SPT group (MX plus SPT 80-100mg daily) and MX+MN group (MX plus MN every two weeks, 12 sessions). The change from the baseline to week 24 was assessed in hair growth (hair density and diameter under dermoscope), scalp tissue structure (epidermal thickness, dermis thickness and average hair follicle diameter under ultrasound biomicroscopy), physician’s global assessment (using a 7-point global-assessment scale, Sinclair’s stage change), patient evaluation (Women's Androgenetic Alopecia Quality of Life Questionnaire and Sinclair’s hair-shedding score) and side effects. Results: 115 participants completed the trial. At week 24, the hair density increased most in MX + MN group and increased least in MX group (p < 0.001for MX + MN group vs MN + SPT group; p = 0.009 for MN + SPT group vs MX group). The hair shaft diameter significantly increased in all groups (p < 0.001, respectively), but there were no significant differences among three groups (p = 0.905). The epidermal thickness and average hair follicle diameter only increased in MX + MN group. Dermis thickness increased in all groups, but there were no significant differences among three groups. Both physician's and patient assessment showed improvement in all three groups. Scalp pruritus was the most common side effect. The MX + SPT group had the most reported adverse effects. Conclusions: topical MX combined with MN is a better choice than either MX plus oral SPT or MX alone for the treatment of mild-to-moderate FPHL patients.